Production Efficiency of Ribbon-Type Sections by the Drawing Method in Doubled-Roll Roller Dies - RAZDOBREEV, V.; KLUYCHNIKOV, K.; LESCHENKO, A.; PALAMAR, D.; VOROBEI, S. (Science and Innovation, 2023)
Introduction. The process of drawing is used to produce a wide range of fashion sections of complex configuration, including thin-walled, ribbon-type, and periodical section profiles. Problem Statement. Because of the complexity of steel ribbon production with flattening machines and high capital intensity of flattening production, since the second half of last century, the manufacturers have been trying to use alternative methods of flattening, in particular drawing in monolithic and double-roll roller dies. Purpose. The purpose of this research is to establish regularities of the influence of different sizing systems and process parameters on the regularities of shape change and energy-force parameters of the drawing process in double-roll roller dies and to determine the most effective schemes for achieving the maximal metal expansion while producing ribbon-type sections. Material and Methods. The materials used are as follows: round billets of 5.9 mm in diameter, made of steel brand St.08А; the methods used are as follows: cool billet processing with varying crimping in the double-roll rol ler die with different gauge systems. Results. The regularities of metal shape change and energy-force parameters alternation of the ribbon-type sec tion drawing process in doubled double-roll roller dies by using different gauge systems have been established. Marginal conditions of the deformation in double-roll dies, which provide stable and smooth drawing process according to the criterion of deformed metal safety factor, have been studied experimentally. The most efficient gau ge system of doubled roller dies, which provides maximal metal expansion while producing ribbon-type sections have been determined experimentally. Conclusions. It has been proposed to use the metal drawing technology in doubled double-roll roller dies with “bullhead-accelerated gauge” system while producing ribbon-type sections with a width-to-thickness ratio of more than 2, for achieving the maximal metal expansion per transition. In addition, such a process is energy efficient as the force of pulling through the roller die decreases.